Penerapan Model Project Based Learning Pada Pembelajaran IPA untuk Meningkatkan Keterampilan Proses Sains Peserta Didik SMPN 30 Muaro Jambi : (Application of Project Based Learning Model in Science Learning to Improve Students' Science Process Skills SMPN 30 Muaro Jambi) - Lidia Siswanti; Yusnaidar Yusnaidar; Agus Subagyo (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The results of the initial observations showed that the low science process skills of students were caused because students were rarely involved in learning activities. The low science process skills of students in low student learning outcomes. The 21st century learning model that is recommended to be used in the 2013 curriculum that can be applied in improving students' science process skills is a project-based learning model. This study aims to analyze the science process skills of class VIII A students of SMPN 30 Muaro Jambi in science learning by applying the Project Based Learning (PjBL) learning model. This research uses Classroom Action Research (CAR). The results showed that the science process skills of grade VIII A students of SMPN 30 Muaro Jambi improved after the project-based learning model was applied. It is concluded that the project-based learning model can improve students' science process skills. Keywords: Science Process Skills, PjBL, SMP ABSTRAK Observasi pendahuluan menunjukkan rendahnya keterampilan proses sains peserta didik disebabkan karena peserta didik jarang dilibatkan dalam aktivitas pembelajaran. Rendahnya KPS peserta didik mengakibatkan hasil belajar peserta didik ikut rendah. Model pembelajaran abad 21 yang direkomendasikan penggunaannya dalam kurikulum 2013 yang dapat diterapkan untuk meningkatkan keterampilan proses sains peserta didik adalah model project based learning. Penelitian ini bertujuan untuk menganalisis keterampilan proses sains peserta didik kelas VIII A SMPN 30 Muaro Jambi pada pembelajaran IPA dengan menerapkan model pembelajaran Project based Learning. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) . Hasil penelitian menunjukkan bahwa keterampilan proses sains peserta didik kelas VIII A SMPN 30 Muaro Jambi meningkat setelah menerapkan model pembelajaran project based learning.Disimpulkan bahwa model project based learning dapat meningkatkan keterampilan proses sains peserta didik. Kata kunci: Keterampilan Proses Sains, PjBL, SMP